The Continuous Strength Method – Review and outlook. (15th January 2023) - Gardner, Leroy; Yun, Xiang; Walport, Fiona
Highlights: The Continuous Strength Method (CSM) is a strain based structural design approach. The background and state of the art of the CSM is reviewed. The CSM features in a number of European and US structural design standards. The range of applicability and key advantages of the CSM are highlighted. Aspects of the CSM that require further research are identified. Abstract: The Continuous Strength Method (CSM) is a deformation-based approach to the design of structures that enables a continuous, rational and accurate allowance for material nonlinearity (i.e. the spread of plasticity and strain hardening). Central to the method is the application of strain limits, determined on the basis of the local slenderness of full cross-sections, to define the resistance of a structural member or system. The method can be applied to structures formed using different materials (e.g. steel, stainless steel or aluminium) and manufacturing processes (e.g. hot-rolled or cold-formed) through the assignment of suitable stress–strain relationships, and can be used for steel–concrete composite design and in fire scenarios. In composite construction, the CSM enables a more rigorous assessment to be made of the development of strength in the structural system taking due account of compatibility between the constituent materials. The design method enables enhancements in structural efficiency and, unlike traditional approaches, allows the assessment of both strength and ductility (which is particularly relevant for high strength steel) demands at the ultimate limit state. For hand calculations, a set of straightforward CSM design equations have been developed. Recognising the increasing importance and use of advanced analysis (i.e. GMNIA), recent research, summarised herein, has focussed on integration of the CSM strain limits into a framework of design by second order inelastic analysis, where the benefits of the method become even more substantial. This paper provides a review of the background and recent developments to the CSM, including incorporation into design standards. Current and ongoing research to expand the scope of the CSM is summarised and recommendations for future work are also set out.